Gender Role Dynamics in Economic Development: Challenges and Opportunities for Women's Empowerment - Daffa, Deandra Rafiq; Arthuro, Dave; Fernanda, Jovanes Agus; Pratama, Muh. Bintang Widya (LPPPIPublishing, 2024)
The role of gender in economic development has become a major concern in the context of women's empowerment. This article investigates those dynamics with a focus on the challenges and opportunities faced in women's economic empowerment efforts. Through a comprehensive review of the literature, we explore the role of gender in economic development, explain the various challenges women face in access and control of economic resources, and identify opportunities to increase their empowerment. We also discuss the impact of gender roles in the context of global and regional economic development.